Paracrine Wnt signaling is necessary for prostate epithelial proliferation. Issue 5 (11th January 2022) - Wei, Xing; Roudier, Martine P.; Kwon, Oh‐Joon; Lee, Justin Daho; Kong, Kevin; Dumpit, Ruth; True, Lawrence; Morrissey, Colm; Lin, Daniel W.; Nelson, Peter S.; Xin, Li
Abstract: Introduction: The Wnt proteins play key roles in the development, homeostasis, and disease progression of many organs including the prostate. However, the spatiotemporal expression patterns of Wnt proteins in prostate cell lineages at different developmental stages and in prostate cancer remain inadequately characterized. Methods: We isolated the epithelial and stromal cells in the developing and mature mouse prostate by flow cytometry and determined the expression levels of Wnt ligands. We used Visium spatial gene expression analysis to determine the spatial distribution of Wnt ligands in the mouse prostatic glands. Using laser‐capture microscopy in combination with gene expression analysis, we also determined the expression patterns of Wnt signaling components in stromal and cancer cells in advanced human prostate cancer specimens. To investigate how the stroma‐derived Wnt ligands affect prostate development and homeostasis, we used a Col1a2‐CreER T2 mouse model to disrupt the Wnt transporter Wntless specifically in prostate stromal cells. Results: We showed that the prostate stromal cells are a major source of several Wnt ligands. Visium spatial gene expression analysis revealed a distinct spatial distribution of Wnt ligands in the prostatic glands. We also showed that Wnt signaling components are highly expressed in the stromal compartment of primary and advanced human prostate cancer. Blocking stromal Wnt secretion attenuated prostate epithelial proliferation and regeneration but did not affect cell survival and lineage maintenance. Discussion: Our study demonstrates a critical role of stroma‐derived Wnt ligands in prostate development and homeostasis.